Search for the Bc meson in hadronic Z decays - BARATE, R. (Institutional Knowledge at Singapore Management University, 1997)
A search for the Bc meson decaying into the channels Jψπ+ and Jψℓ+νℓ (ℓ = e or μ) is performed in a sample of 3.9 million hadronic Z decays collected by the ALEPH detector. This search results in the observation of 0 and 2 candidates in each of these channels, respectively, while 0.44 and 0.81 background events are expected. The following 90% confidence level upper limits are derived:Br(Z→BcXBr(Z→qq̄Br(Bc+→Jψπ+)